Formula and production process for improving heat conduction performance of phase change material and secondary refrigerant
By adding graphene powder and inorganic thermal conductivity additives to the phase change material, combining polymer matrix and low-temperature cooling materials, the problems of low thermal conductivity and unstable phase change temperature in traditional phase change materials are solved, and composite materials with high thermal conductivity and good phase change characteristics are achieved, which are suitable for efficient thermal management and cooling systems.
Patent Information
- Application Number
- CN202411593214.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-03-25
AI Technical Summary
The thermal conductivity of traditional phase change materials is low, resulting in heat not being able to conduct quickly and effectively, causing temperature fluctuations and affecting the thermal management of the system. At the same time, the phase change temperature is unstable, the mechanical strength is insufficient, and it is prone to rupture or failure.
By adding graphene powder and inorganic thermal conductivity additives to the phase change material, combining polymer matrix and low-temperature cooling materials, specific production process steps, such as segmented heating, ultrasonic treatment and airflow stirring, form composite materials with high thermal conductivity and good phase change characteristics.
It significantly improves the thermal conductivity of the composite material, enhances the thermal conductivity of the material, avoids equipment overheating, extends service life, and maintains good phase change characteristics and mechanical strength.
Smart Images

Figure CN119684975A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material processing, and in particular to a formula and a production process for improving the thermal conductivity of a phase change material and a coolant. Background Art
[0002] According to a high thermal conductivity composite hydrated salt phase change heat storage material and its preparation method disclosed in Chinese patent publication number "CN110079278A", the raw material composition mass percentage is: hydrated salt 60%-75%, additive 0.5%-5%, adsorbent 10%-20%, thermal conductor 10-30%. During preparation, according to the formula ratio, weigh the hydrated salt and additive and stir evenly, then add the adsorbent, mix evenly with a powder beater, seal, place in a blast oven and heat until completely melted; after cooling, use a powder beater to crush, add the thermal conductor and stir evenly, and press to form.
[0003] According to a solid-solid phase change material design method, solid-solid phase change material and its configuration method disclosed in Chinese patent publication number "CN116631544A", it includes obtaining climate data and pavement structure type of the target area, constructing a finite element model of the pavement temperature field, establishing the relationship between climate data and pavement structure type and solid-solid phase change material performance parameters, and obtaining the solid-solid phase change material performance parameters in the target area. The solid-solid phase change material formula includes: soft segment material, hard segment material, cross-linking agent, chain extender, and carbon-based material.
[0004] According to the high thermal conductivity polyurethane solid-solid phase change material and its preparation method disclosed in the Chinese patent publication number "CN108383968B", the mass percentage of its formula composition is: polyethylene glycol: 60% to 95%; isocyanate: 2% to 30%; chain extender: 0% to 9%; surfactant: 0% to 5%; thermal conductive medium: 0.5% to 8%. The present invention also discloses a preparation method of the high thermal conductivity polyurethane solid-solid phase change material. The present invention uses expanded graphite with a large porosity as a carrier and a thermal conductive medium, and uses a polyurethane material with a phase change function as a matrix. Through physical loading and chemical cross-linking, the three functions of adsorption loading, steady-state shaping and construction of a thermal conductive channel are cleverly combined to obtain a high thermal conductivity phase change energy storage material with high phase change latent heat, good thermal stability and a fast thermal response rate.
[0005] Today, we live in a society with highly developed mechanical equipment. When a large number of equipment such as engines and generators generate a large amount of heat energy during operation, it is far from enough to rely on cooling fans alone. Liquid media are generally used for cooling. But in fact, the thermal conductivity of the liquid media used is very low, but it is many times better than wind cooling. When cooling a car engine, if wind cooling can only cool one surface, the liquid medium can cool all surfaces, and the thermal conductivity of wind is only a few tenths of that of liquid. In the fields of aerospace, refrigeration, etc., ultra-efficient cooling systems can not only improve the cooling effect, but also reduce the weight and volume of the cooling system. It has special significance in the military field. In the field of refrigeration and freezing, it can greatly save energy and greatly improve the quality of frozen products.
[0006] 1. In traditional phase change materials, the thermal conductivity is often low, resulting in the inability to conduct heat quickly and effectively, causing temperature fluctuations and affecting the thermal management of the system;
[0007] 2. Under different environmental conditions, the phase change temperature of traditional phase change materials may be unstable, affecting their application effects, and their mechanical strength is insufficient, making them prone to cracking or failure. Summary of the invention
[0008] Technical issues solved
[0009] In view of the shortcomings of the prior art, the present invention provides a formula and production process for improving the thermal conductivity of phase change materials and coolants, solving the following problems:
[0010] In traditional phase change materials, thermal conductivity is often low, resulting in heat not being able to be conducted quickly and effectively, causing temperature fluctuations and affecting the thermal management of the system. Under different environmental conditions, the phase change temperature of traditional phase change materials may be unstable, affecting their application effects. Insufficient mechanical strength and easy to break or fail are two problems.
[0011] Technical Solution
[0012] To achieve the above objectives, the present invention is implemented through the following technical solutions: a formula for improving the thermal conductivity of phase change materials and coolants, the formula comprising phase change materials, graphene powder, a polymer matrix, a low-temperature coolant and a thermal conductive additive, the addition ratio of the graphene powder is one thousandth to 20%, the low-temperature coolant includes propylene glycol, calcium chloride solution, ethylene glycol solution, after ethylene glycol is mixed with water, the freezing point of the solution can be lowered, and it is suitable for refrigeration systems in the medium and low temperature range, ethanol solution (alcohol), ethanol solution has a lower freezing point, suitable for lower temperature environments, methanol solution: the freezing point of methanol solution is lower, suitable for ultra-low temperature environments, sodium chloride solution: after sodium chloride is dissolved in water, the freezing point can be lowered, and the cost is low, potassium formate solution: has a lower freezing point and good thermal conductivity, low viscosity, potassium acetate solution: low freezing point, good thermal conductivity, environmentally friendly, silicone oil: has a wider liquid temperature range, good chemical stability, and is non-conductive.
[0013] Preferably, the phase change material is an organic phase change material, and the phase change material is hexadecanoic acid, heptadecanoic acid or a mixture of the two in any proportion, and the mass percentage of the phase change material in the total formula is 30% to 70%.
[0014] Preferably, the thermal conductive additive is an inorganic thermal conductive powder, specifically boron nitride, aluminum oxide or a mixture of the two in any proportion, and the mass percentage of the thermal conductive additive in the total formula is 5% to 25%.
[0015] Preferably, the addition ratio of the graphene powder is 0.5 to 10%, and the number of structural layers of the graphene powder is from a single layer to twenty layers, and the thickness ranges from 0.3 to 10 nanometers.
[0016] Preferably, the polymer matrix is polyvinyl alcohol, polystyrene or a copolymer thereof, and the mass percentage of the polymer matrix in the total formulation is 10% to 30%.
[0017] Preferably, the production process steps are as follows:
[0018] Sp1: Prepare the required raw materials, including phase change materials, graphene powder, thermal conductive additives and polymer matrix;
[0019] Sp2: In a clean mixing container, first heat the phase change material to its molten state, and control the temperature at 50°C to 70°C;
[0020] Sp3: gradually add graphene powder to the molten phase change material, stir evenly, and continue stirring for 10 minutes;
[0021] Sp4: Add thermal conductive additive and continue stirring for 10 to 15 minutes;
[0022] Sp5: Add polymer matrix to the mixture and stir for 5 to 10 minutes;
[0023] Sp6: The mixture produced in Sp5 was transferred to an ultrasonic mixer and subjected to ultrasonic treatment for 10 to 30 minutes;
[0024] Sp7: The product treated by Sp6 is cooled to room temperature and collected by forming.
[0025] Preferably, in the Sp2, segmented heating is adopted, and the phase change material is first preheated at a low temperature of 50° C. for 30 minutes to remove moisture and volatile impurities, and then the temperature is raised to 60° C. to 70° C. for melting.
[0026] Preferably, in the Sp3, the graphene powder is subjected to ultrasonic spray drying treatment before being added to prepare nanoparticles, and during the addition process, the graphene powder is evenly dispersed into the molten phase change material by spraying.
[0027] Preferably, in the above Sp4, a surfactant is added to the thermal conductive agent during the mixing process to improve the interfacial affinity between the thermal conductive agent and the phase change material, and air flow stirring is adopted.
[0028] Preferably, in the Sp6, the mixture is cooled through a closed circuit immediately after the ultrasonic treatment, so that the microstructure formed by the mixture under the action of the ultrasonic wave is locked during the rapid cooling. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a stress-strain curve diagram of the present invention;
[0030] Figure 2 It is the material displacement distribution diagram of the present invention.
[0031] Beneficial Effects
[0032] The present invention provides a formula and a production process for improving the thermal conductivity of a phase change material and a coolant.
[0033] It has the following beneficial effects:
[0034] 1. The present invention significantly improves the thermal conductivity of the composite material by adding graphene powder and inorganic thermal conductive additives. The high thermal conductivity of graphene can form a good thermal conductive network in the material, so that heat can be transmitted more quickly and evenly in the material. The enhanced thermal conductivity is crucial for applications that require rapid heat dissipation, which can effectively avoid overheating of equipment and extend the service life. The enhanced thermal conductivity is crucial for applications that require rapid heat dissipation, which can effectively avoid overheating of equipment and extend the service life. It is mainly used for various refrigerants, heat exchangers, phase change materials (including high temperature, low temperature), water, salt water, silicone oil, automobiles, antifreeze for various vehicles, etc.
[0035] 2. The present invention uses hexadecanoic acid and heptadecanoic acid as phase change materials. These organic phase change materials have high phase change latent heat at a specific temperature. Phase change materials can maintain a relatively stable temperature when absorbing and releasing heat, making them very suitable for use in cooling systems. Experimental data show that when the mass ratio of phase change materials is between 30% and 70%, its phase change latent heat can reach more than 130kJ / kg, which can effectively adjust the indoor temperature and reduce energy consumption.
[0036] 3. The present invention adopts the use of polymer matrix (including polyvinyl alcohol or polystyrene) to provide good mechanical strength and stability. Experiments show that adding 10% to 30% of polymer matrix can effectively prevent the material from decomposing or failing under high temperature or extreme conditions. This enhances the durability of the material in practical applications, reduces the frequency of maintenance and replacement, saves costs, improves the overall strength and stability of the material, and enables the material to withstand greater pressure and external conditions in actual use. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Specific embodiment one:
[0039] A formula for improving the thermal conductivity of a phase change material and a coolant, a formula for improving the thermal conductivity of a phase change material and a coolant, the formula comprising a phase change material, graphene powder, a polymer matrix, a low-temperature coolant material and a thermal conductive additive, the addition ratio of the graphene powder is 1‰ to 20%, the low-temperature coolant material comprises any one or more combinations of propylene glycol, calcium chloride solution, ethylene glycol solution, ethanol solution, methanol solution, sodium chloride solution, potassium formate solution, potassium acetate solution, and silicone oil, and graphene oxide is additionally added to the low-temperature coolant material, so as to achieve a thermal conductivity of the entire material of 1‰-20%.
[0040] The phase change material is an organic phase change material, and the phase change material is hexadecanoic acid, heptadecanoic acid or a mixture of the two in any proportion, and the mass percentage of the phase change material in the total formula is 30% to 70%.
[0041] The thermal conductive additive is an inorganic thermal conductive powder, specifically boron nitride, aluminum oxide or a mixture of the two in any proportion. The mass percentage of the thermal conductive additive in the total formula is 5% to 25%.
[0042] The addition ratio of graphene powder is 0.5 to 10%, and the number of layers of the graphene powder structure is from a single layer to twenty layers. The thickness ranges from 0.3 to 10 nanometers.
[0043] The polymer matrix is polyvinyl alcohol, polystyrene or a copolymer thereof, and the mass percentage of the polymer matrix in the total formula is 10% to 30%.
[0044] Phase change materials (PCMs) are substances that absorb or release heat at a specific temperature. When the temperature rises, they absorb heat and turn into a liquid state, and when the temperature drops, they release heat and return to a solid state. This property makes them very promising for applications in temperature control and energy storage. Hexadecanoic acid and heptadecanoic acid undergo phase changes at about 16°C and 18°C, respectively. When the ambient temperature reaches these values, the materials absorb heat, thereby slowing down the temperature increase. This is very useful for applications such as buildings and cooling systems, as they can effectively reduce the burden on air conditioning and heating equipment. These phase change materials absorb solar heat during the day and release it at night, reducing energy demand and improving the energy efficiency of buildings. In smart buildings, the use of phase change materials can reduce electricity consumption during peak power consumption. Since these materials are usually organic, they are safe to use and non-toxic, meeting modern environmental standards. In electronic devices, they help manage heat and extend the life of equipment. In cold chain transportation, they keep the temperature stable and ensure the safety of food and medicine.
[0045] Graphene is a two-dimensional material composed of a single layer of carbon atoms arranged in a hexagonal pattern. It has excellent thermal conductivity, strength and electrical conductivity. Graphene's thermal conductivity is much higher than that of conventional metals, and it can quickly conduct heat, thereby improving the thermal conductivity of the overall material. After adding graphene powder, the thermal conductivity of the composite material will be significantly improved to avoid overheating. Graphene has extremely high mechanical strength and can enhance the overall structure of the composite material, making it more durable and adaptable to various working conditions. Compared with metal materials, graphene has a lower density, which can help reduce the overall weight of the material and is suitable for applications in aerospace and other fields. In thermal management systems, it is used as a thermally conductive filler to enhance the thermal conductivity of the material. In composite materials, it improves strength and durability, and is suitable for high-demand fields such as aviation and automobiles.
[0046] The polymer matrix is the foundation of composite materials, providing structural support and bonding properties. The polymer matrix provides the necessary structural strength for composite materials, allowing them to maintain their shape and stability during use. The polymer matrix helps to firmly bind the other components and ensure that the material can maintain its performance under different temperatures and pressures. In buildings and home appliances, it acts as a thermal insulation and insulation material. In electronic products, it acts as a packaging material to provide protection and insulation.
[0047] Thermal conductive additives are important ingredients to further enhance thermal conductivity. Boron nitride and aluminum oxide both have good thermal conductivity, can form an effective heat conduction network, and improve the overall thermal conductivity of the material. These inorganic materials can remain stable in high temperature environments without decomposition or damage, and are suitable for high temperature applications. In electronic heat dissipation materials, they help to quickly dissipate heat and protect components. In high temperature processes, they ensure material stability and reliability.
[0048]
[0049] Improved thermal conductivity: As the proportion of graphene increases, the thermal conductivity of the composite material increases significantly. In particular, when the graphene addition ratio reaches 10% and above, the thermal conductivity exceeds 0.75W / m·K, showing good thermal conductivity. Phase change characteristics: Although the addition of graphene improves thermal conductivity, the phase change temperature and latent heat decrease slightly. This shows that the addition of graphene affects the heat storage capacity of the phase change material to some extent. A graphene ratio of 5%-10% is selected to balance thermal conductivity and phase change characteristics, ensuring that the material can effectively regulate temperature while maintaining good energy storage capacity. Specific embodiment 2:
[0051] A production process for improving the thermal conductivity of phase change materials and coolants.
[0052] The production process steps are as follows:
[0053] Sp1: Prepare the required raw materials, including phase change materials, graphene powder, thermal conductive additives and polymer matrix;
[0054] Sp2: In a clean mixing container, first heat the phase change material to its molten state, and control the temperature at 50°C to 70°C;
[0055] Sp3: gradually add graphene powder to the molten phase change material, stir evenly, and continue stirring for 10 minutes;
[0056] Sp4: Add thermal conductive additive and continue stirring for 10 to 15 minutes;
[0057] Sp5: Add polymer matrix to the mixture and stir for 5 to 10 minutes;
[0058] Sp6: The mixture produced in Sp5 was transferred to an ultrasonic mixer and subjected to ultrasonic treatment for 10 to 30 minutes;
[0059] Sp7: The product treated by Sp6 is cooled to room temperature and collected by forming.
[0060] In Sp2, segmented heating is used, and the phase change material is first preheated at a low temperature of 50°C for 30 minutes to remove moisture and volatile impurities, and then the temperature is raised to 60°C to 70°C for melting.
[0061] In Sp3, the graphene powder is prepared into nanoparticles by ultrasonic spray drying before being added, and the graphene powder is evenly dispersed into the molten phase change material by spraying during the addition process.
[0062] In Sp4, a surfactant is added to the thermal conductive agent during the mixing process to improve the interfacial affinity between the thermal conductive agent and the phase change material, and air flow stirring is used.
[0063] In Sp6, the mixture is cooled immediately through a closed circuit after ultrasonic treatment, so that the microstructure formed by the mixture under the action of ultrasound is locked during rapid cooling.
[0064] During the mixing stage, the phase change material (including but not limited to hexadecanoic acid and heptadecanoic acid), graphene powder, polymer matrix and thermal conductive additive are mixed in proportion. The key control nodes include the precise proportion of the ingredients and the mixing time. The purpose of controlling the proportion of the ingredients is to ensure that each material is evenly distributed to avoid excessive or insufficient local content, which affects the thermal conductivity and phase change characteristics of the material. The control of mixing time is to ensure sufficient contact between the materials to promote interaction. If the mixing is uneven, the thermal conductivity of the phase change material may be insufficient, thus affecting the final application effect.
[0065] During the heating stage, the heating temperature and time need to be strictly monitored. The heating temperature must be higher than the melting point of the phase change material, but not higher than its decomposition temperature, so as to ensure that the material remains chemically stable. The heating time is controlled to ensure that the phase change material is completely melted and fully integrated with other components. The technical improvement of this process lies in optimizing the heating parameters to ensure that the material has better fluidity in the molten state, so that the components can be evenly mixed, thereby improving the overall performance of the final material.
[0066] When entering the cooling stage, it is crucial to control the cooling rate. Slow cooling can prevent the generation of internal stress and ensure that the material has good mechanical properties and thermal conductivity after solidification. Improper cooling may cause cracks or unevenness in the material, which will affect its service life and thermal conductivity. The technical improvement at this stage optimizes the cooling rate so that the material maintains a uniform structure during the cooling process, further improving its thermal performance.
[0067] Throughout the entire process, all control measures are aimed at achieving the best performance of the final product. Examples include, but are not limited to, properly designed mixing, heating and cooling processes that can significantly improve the thermal conductivity and phase change efficiency of the material. This means better thermal management, improved energy efficiency and service life for applications in building materials or electronic devices.
[0068] At each stage, although no obvious by-products are usually produced, it is still necessary to pay attention to possible volatile substances and solid particles. If the mixing is not uniform or the heating temperature is too high, some ingredients may decompose and produce gases or other unnecessary compounds. Therefore, controlling process parameters and monitoring the reaction process can ensure the minimization of by-products and ensure the purity and performance of the final product. Specific embodiment three:
[0070] Further experimental data are as follows:
[0071]
[0072] Through the analysis of experimental data, it can be seen that the thermal conductivity is positively correlated with the addition ratio of graphene powder and thermal conductive additive. As the proportion of graphene increases, the thermal conductivity of the material also increases significantly. This is because the excellent thermal conductivity of graphene effectively enhances the overall thermal conductivity of the composite material.
[0073] The change of phase change temperature is relatively stable, which is mainly affected by the characteristics of the phase change material itself. The latent heat of phase change decreases with the increase of the proportion of thermal conductive additive, which may be related to the change of physical properties of thermal conductive additive at high temperature.
[0074] Performance improvement: By adding graphene and thermal conductive additives, the thermal conductivity of the composite material is significantly improved, which can respond to ambient temperature changes more quickly and is suitable for high-efficiency temperature control applications.
[0075] Phase change properties: Phase change materials exhibit good phase change properties under different component ratios and can effectively store and release heat at a specific temperature.
[0076] Wide applicability: This formula and process are suitable for fields such as building materials, heat dissipation management of electronic equipment and cold chain logistics, and have good market application prospects.
[0077] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the statement "comprising a reference structure" do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0078] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A formula for improving the thermal conductivity of phase change materials and coolants, characterized in that: The formula includes phase change material, graphene powder, polymer matrix, low-temperature cooling material and thermal conductive additive, the addition ratio of the graphene powder is one thousandth to 20%, and the low-temperature cooling material includes any one or more combinations of propylene glycol, calcium chloride solution, ethylene glycol solution, ethanol solution, methanol solution, sodium chloride solution, potassium formate solution, potassium acetate solution and silicone oil.
2. A formula for improving the thermal conductivity of phase change materials and coolants according to claim 1, characterized in that: The phase change material is an organic phase change material, and the phase change material is hexadecanoic acid, heptadecanoic acid or a mixture of the two in any proportion, and the mass percentage of the phase change material in the total formula is 30% to 70%.
3. A formula for improving the thermal conductivity of phase change materials and coolants according to claim 1, characterized in that: The thermal conductive additive is an inorganic thermal conductive powder, specifically boron nitride, aluminum oxide or a mixture of the two in any proportion. The mass percentage of the thermal conductive additive in the total formula is 5% to 25%.
4. A formula for improving the thermal conductivity of phase change materials and coolants according to claim 1, characterized in that: The addition ratio of the graphene powder is 0.5 to 10%, and the number of structural layers of the graphene powder is from a single layer to twenty layers, and the thickness ranges from 0.3 to 10 nanometers.
5. A formula for improving the thermal conductivity of phase change materials and coolants according to claim 1, characterized in that: The polymer matrix is polyvinyl alcohol, polystyrene or a copolymer thereof, and the mass percentage of the polymer matrix in the total formula is 10% to 30%.
6. A production process for improving the thermal conductivity of a phase change material and a coolant according to any one of claims 1 to 5, characterized in that: The production process steps are as follows: Sp1: Prepare the required raw materials, including phase change materials, graphene powder, thermal conductive additives and polymer matrix; Sp2: In a clean mixing container, first heat the phase change material to its molten state, and control the temperature at 50°C to 70°C; Sp3: gradually add graphene powder to the molten phase change material, stir evenly, and continue stirring for 10 minutes; Sp4: Add thermal conductive additive and continue stirring for 10 to 15 minutes; Sp5: Add polymer matrix to the mixture and stir for 5 to 10 minutes; Sp6: The mixture produced in Sp5 was transferred to an ultrasonic mixer and subjected to ultrasonic treatment for 10 to 30 minutes; Sp7: The product treated by Sp6 is cooled to room temperature and collected by forming.
7. The production process of a formula for improving the thermal conductivity of a phase change material and a coolant according to claim 6, characterized in that: In the Sp2, segmented heating is adopted, and the phase change material is firstly preheated at a low temperature of 50°C for 30 minutes to remove moisture and volatile impurities, and then the temperature is raised to 60°C to 70°C for melting.
8. The production process of a formula for improving the thermal conductivity of a phase change material and a coolant according to claim 6, characterized in that: In the Sp3, the graphene powder is subjected to ultrasonic spray drying treatment before being added to prepare nanoparticles, and is evenly dispersed into the molten phase change material by spraying during the addition process.
9. According to the production process of a formula for improving the thermal conductivity of phase change materials and coolants as described in claim 6, in the Sp4, a surfactant is added to the thermal conductive agent during the mixing process to improve the interface affinity between the thermal conductive agent and the phase change material, and air flow stirring is used.
10. The production process of a formula for improving the thermal conductivity of phase change materials and coolants according to claim 6, characterized in that: In the Sp6, the mixture is cooled through a closed circuit immediately after the ultrasonic treatment, so that the microstructure formed by the mixture under the action of the ultrasonic wave is locked during the rapid cooling.
Citation Information
Patent Citations
High thermal conductivity polyurethane solid-solid phase change materials and their preparation methods
CN108383968B
Cited By
Intelligent building envelope dynamic temperature adjusting system based on reinforcement learning
CN120909365A
Intelligent building envelope dynamic temperature regulating system based on reinforcement learning
CN120909365B